Análise da influência dos movimentos antivacina e da hesitação vacinal sobre a cobertura vacinal no Brasil nos últimos 20 anos: achados de uma revisão bibliográfica narrativa - SOBREIRA, André Luís Rodrigues (2023)
Vaccination is recognized as one of the most successful and most cost-effective public health interventions, being responsible for the eradication of smallpox and for the control and prevention of several immunopreventable diseases, such as childhood polio, diphtheria, tetanus and whooping cough, all around the world. In Brazil, as of 1973, the National Immunization Program (PNI) was formulated, regulated by Federal Law No. 6,259, of October 30, 1975, and by Decree No. 78,321, of August 12, 1976, which instituted the National Epidemiological Surveillance System (SNVE), which in itself already allows for a uniform vaccination schedule, the sustainable introduction of innovative vaccines, technical standardization and new routine vaccination strategies. However, the reappearance of eradicated diseases such as measles in Roraima and Amazonas in 2017, aims to draw attention to the event of vaccine hesitation, and how it can originate from false news and anti-vaccine movements. Objective: To analyze the influence of anti-vaccine movements and vaccine hesitation on vaccination coverage in Brazil, in works published in the literature between 2001 and 2021. Material and Methods: The present study is a narrative review, of a descriptive character, featuring a qualitative approach. The data will be collected from the bibliographic survey in the Lilacs, Scielo, Pubmed and Google academic databases, using the following descriptors: vaccination hesitation; anti-vaccine; vaccination coverage, with the purpose of compiling information related to the study theme, in Brazil, in the last 20 years (from 2001 to 2021) Results: By analyzing the articles, it is possible to observe a reduction in vaccination coverage in the Brazilian territory, however the explanations given for this retraction are varied, and there is little academic research regarding vaccine hesitation and facts that can lead to it such as false news. However, approximately 17% of the documents issued agree that false news has a direct or indirect influence on the increase in vaccine hesitation. Conclusion: The Brazilian vaccine coverage has been declining in the last decade, however it has not been established in direct relation with the event of vaccine hesitation. However, false news regarding vaccinations and anti-vaccination movements can negatively impact an individual's chance of getting vaccinated. Therefore, introducing lay people with transparent and positive information about vaccination, as well as avoiding antagonizing groups against immunization, can minimize the impact of false news and produce a virtual space more receptive to vaccination.